2011
DOI: 10.1103/physrevb.83.075119
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiocalculations for theβ-tin diamond transition in silicon: Comparing theories with experiments

Abstract: We investigate the pressure-induced metal-insulator transition from diamond to β-tin in bulk Silicon, using quantum Monte Carlo (QMC) and density functional theory (DFT) approaches. We show that it is possible to efficiently describe many-body effects, using a variational wave function with an optimized Jastrow factor and a Slater determinant. Variational results are obtained with a small computational cost and are further improved by performing diffusion Monte Carlo calculations and an explicit optimization o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 56 publications
1
35
0
6
Order By: Relevance
“…7,8 There have been dramatic theoretical advances in the quality of the variational wave function during the last decade, so that it is now possible to achieve chemical accuracy for atoms, ions, small molecules, and even periodic systems. [17][18][19][20][21] These quantitative improvements have been made possible by new stochastic optimization techniques, which can optimize variational wave functions depending on hundreds of free parameters. 22 In our variational calculations, we have used a Jastrowantisymmetrized geminal power (JAGP) variational wave function for N (even) interacting electrons, 18,19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 There have been dramatic theoretical advances in the quality of the variational wave function during the last decade, so that it is now possible to achieve chemical accuracy for atoms, ions, small molecules, and even periodic systems. [17][18][19][20][21] These quantitative improvements have been made possible by new stochastic optimization techniques, which can optimize variational wave functions depending on hundreds of free parameters. 22 In our variational calculations, we have used a Jastrowantisymmetrized geminal power (JAGP) variational wave function for N (even) interacting electrons, 18,19 …”
Section: Methodsmentioning
confidence: 99%
“…(3) are variational parameters to be optimized. However, by taking advantage of the symmetries of the periodic linear chain, 21 and by using an alternative, minimal expansion in terms of molecular orbitals, 19 the actual number of independent variational parameters to optimize is reduced, so that the optimization can be effectively performed by the method described in Ref. 22.…”
Section: Methodsmentioning
confidence: 99%
“…The same instability problem is reported in the Si pressure induced phase transition from diamond to β-tin structure 18,35,37 , where the high pressure structure (β-tin) is also metallic, similar to our B1 structure case 9 . We have carefully investigated the dependence on the grid coarseness of kmesh but we found that the instability of the structure does not disappear even if we used a dense mesh.…”
Section: Instabilities Of Structures At Metallic Phasementioning
confidence: 48%
“…The tendency of DMC calibrations over DFT for the present GaAs case is consistent with those for Si bulk properties and the transition pressure. 18,19,37 The shift by DMC calibration is established as resulting from the larger correction for the energy of metallic phase (higher density phase) than that of lower density phase, making the common tangent on the dependence of free energies on system volumes steeper. We have investigated the phonon contributions to the prediction.…”
Section: Discussionmentioning
confidence: 99%
“…При дальнейшем сжатии структура β-Sn переходит в другие более плотные полиморфные модификации. И хотя было предложено много теорети-ческих методов расчета уравнения состояния различных кристаллических модификаций Si и Ge [8][9][10][11][12], природа барической металлизации не вполне ясна. В частности, неясна природа необратимости ФП из алмазной струк-туры (cd-фаза) в структуру β-Sn (tin-фаза).…”
Section: Introductionunclassified